Foucault and history in organization studies - Rowlinson, Michael; Carter, Chris (2002)
There is an increasing call for an historical perspective in organiztion studies. Clegg, Jacques and Burrell in particular combine this call with a Foucauldian reformulation of organization studies. But Foucauldians in organization studies have largely ignored the criticisms of Foucault from historians. We rehearse six main criticisms of Foucault from historians: (1) impenetrable style; (2) avoidance of narrative; (3) ambivalence to truth; (4) errors in historical facts; (5) neglect of relevant historiography; and (6) questionable historical explanations. We then apply these criticisms to the work of Clegg, Jacques, and Burrell. Clegg makes serious historical erros, and neglects critisms of labour process historiography. The historical sources and historiography cited by Jacques are insufficient. Burrell's interpretation of the connection between modernity and the Holocaust is questionable in the light of recent historiography. We conclude that so far, the invocation of Foucault has exacerbated the problematic treatment of history in organization studies. - Reproduced.
Keywords: Organizations